2016
DOI: 10.2527/jas.2015-9521
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary fat source and feeding duration on finishing pig growth performance, carcass composition, and fat quality1,2

Abstract: A total of 160 finishing pigs (PIC 327 × 1050; initially 45.6 kg) were used in an 84d experi ment to evaluate the effects of dietary fat source and feeding duration on growth performance, carcass char acteristics, and carcass fat quality. There were 2 pigs per pen with 8 pens per treatment. The 10 dietary treat ments were a corn-soybean meal control diet with no added fat and a 3 × 3 factorial with main effects of fat source (4% tallow, 4% soybean oil, or a blend of 2% tallow and 2% soybean oil) and feeding du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 28 publications
1
27
0
1
Order By: Relevance
“…In accordance with our results, Park et al [ 25 ], in a study testing soybean oil as a lipid source for pig diets, showed that the content of PUFA, especially n-3 FAs, in the carcass can be linearly increased depending on the length of the feeding period of a diet supplemented with soybean oil. Similar findings were obtained by Stephenson et al [ 26 ] who stated that increasing the duration of feeding with soybean oil lowered MUFA and increased PUFA concentrations for all fat depots. When pigs are fed diets with n-3 fatty acids, pork and pork products could be recognized as functional foods with new health-promoting properties [ 27 ].…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with our results, Park et al [ 25 ], in a study testing soybean oil as a lipid source for pig diets, showed that the content of PUFA, especially n-3 FAs, in the carcass can be linearly increased depending on the length of the feeding period of a diet supplemented with soybean oil. Similar findings were obtained by Stephenson et al [ 26 ] who stated that increasing the duration of feeding with soybean oil lowered MUFA and increased PUFA concentrations for all fat depots. When pigs are fed diets with n-3 fatty acids, pork and pork products could be recognized as functional foods with new health-promoting properties [ 27 ].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, livestock producers have studied novel means to manipulate the n-3 PUFA content of their protein products. Stephenson et al (2016) demonstrated the ability of dietary components to alter the fatty acid composition of multiple fat depots within the pig. In the literature, a plethora of studies show dietary ingredients such as linseed/flaxseed and fish oil/meal increased meat n-3 PUFA content in various body adipose depots ( Otten et al, 1993 ; Cherian and Sim, 1995 ; Juarez et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Results from the analysis of carcass compositions and quality showed no significant effect of dietary oil source, or rate of inclusion on pork carcass composition and quality. Stephenson et al (2016) saw no difference as a result of dietary fat source in HCW, loin eye area, and percent yield in pigs. Results from the carcass analysis further supports the case that traditionally dietary oil sources can be replaced successfully with novel high oleic soybean oils, without resulting in deleterious effects on carcass weights and lean meat yields.…”
Section: Discussionmentioning
confidence: 90%
“…The addition of five percent of a variety of animal and plant fat sources had no measurable impact on carcass primal yields, or the percentage of lean and fat from those primal cuts (Apple et al, 2009b). Furthermore, adding beef tallow, soybean oil, or a 50:50 combination of the two at a dietary inclusion rate of four percent had showed no impact across treatments on the hot carcass weight, loin eye area, and percent yield of pigs (Stephenson et al, 2016). While fat source appears not to have an impact on lean carcass yield, the same cannot be said for the amount of fat include in the diet.…”
Section: Pork Carcass Compositionmentioning
confidence: 94%
See 1 more Smart Citation